Romancing the rural: Reconceptualizing rural entrepreneurship as engagement with context(s). (August 2019) - Gaddefors, Johan; Anderson, Alistair R
This article considers how we conceive and research rural entrepreneurship. While we argue for the importance of context for understanding entrepreneuring, we also acknowledge that some perceptions of the rural context may be misleading. We critically review how the rural in rural entrepreneurship has been applied. We find how some romancing of the rural has had detrimental effects in theorizing about rural. However, we also find and discuss the interesting range of relationships between the rural and the entrepreneurship presented in the literature. We conclude that a conceptually robust approach can be achieved by examining the nature and extent of entrepreneurial engagement with the contexts that characterize the rural. Finally, we propose methods that will enable us to achieve better understanding of the processes of rural.